The reported point centromeres of Scheffersomyces stipitis are retrotransposon long terminal repeats. Issue 5 (29th January 2019) - Coughlan, Aisling Y.; Wolfe, Kenneth H.
Abstract: Point centromeres, found in some ascomycete yeasts such Saccharomyces cerevisiae, are very different in structure from the centromeres of other eukaryotes. They are tiny and nonrepetitive and contain only two short conserved sequence motifs. Until recently, point centromeres were thought to have a single evolutionary origin, in the budding yeast family Saccharomycetaceae. Most yeasts outside this family have centromeres that are many kilobases in size. Some have centromeres consisting of a large inverted repeat sequence, others have centromeric clusters of retrotransposons, and a third group including Candida albicans has centromeres with no conserved sequence features. It was recently reported that Scheffersomyces stipitis has point centromeres with a strongly conserved 125‐bp core sequence, which is unexpected because S .  stipitis is only distantly related to the known point‐centromere species. We show here that the 125‐bp core sequence is actually part of the long terminal repeat (LTR) of the Ty5‐like retrotransposon Tps5, which forms a cluster in the centromeric region of each S .  stipitis chromosome. Thus, the LTR of a centromere‐associated retrotransposon confers centromere‐like mitotic stability when cloned into a plasmid. The centromeric regions of S .  stipitis contain three types of Tps5 element (Tps5a, Tps5b, and Tps5c) and a noncoding nonautonomous large retrotransposon derivative.